Application of the theory on planned behaviour to green hotel visit intention: An extension of self-identity - Cheng, Boon Liat *; Enriquez, B. B.; Thomborrow, T.; Mansori, Shaheen (2019)
The demand for green products and services has increased in recent years, as customers are more concerned about global warming and environmental pollution. As a result, more companies focus on introducing environmental friendly solutions such as green concept hotels to meet consumers demand. Since he whole concept of green hotel is still novel in market, this article aims to investigate the relationship between attitude, subjective norms, perceived behavioural control, self-identity and intention to visit green hotels. The findings show that self-identity can enhance the predictive powers of the Theory of Planned Behaviour as it explains an additional variance of 9%. This findings can be useful the players in hospitality industry to promote their offering in market by using more effective marketing tools. Furthermore, this research enhances a growing body of knowledge that recognise self-identity as a genuine addition to the Theory of Planned Behaviour.